2019
DOI: 10.3390/ijms20235982
|View full text |Cite
|
Sign up to set email alerts
|

Parasympathetic Effect Induces Cell Cycle Activation in Upper Limbs of Paraplegic Patients with Spinal Cord Injury

Abstract: The present study aimed to investigate gene expression changes related to cell cycle activation in patients with spinal cord injury (SCI) and to further evaluate the difference between the upper and lower limbs of SCI patients. Fibroblasts were obtained from the upper and lower limbs of SCI patients and healthy subjects. To investigate gene expression profiling in the fibroblasts from SCI patients compared to the healthy subjects, RNA-Seq transcriptome analysis was performed. To validate the parasympathetic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Is well-known that the disruption of the parasympathetic nervous system (PNS) also affects cell proliferation [27,28], and recent findings had confirmed that parasympathetic activity is linked to cell proliferation and cell cycle-related gene expression above the neurological level of injury rather than below it; in which case, the main neurotransmitter involved is the acetylcholine in the upregulation of some genes that participate in the chromosomal instability [29].…”
Section: Is Autonomic Dysreflexia Responsible For Other Comorbidities In Sci?mentioning
confidence: 99%
“…Is well-known that the disruption of the parasympathetic nervous system (PNS) also affects cell proliferation [27,28], and recent findings had confirmed that parasympathetic activity is linked to cell proliferation and cell cycle-related gene expression above the neurological level of injury rather than below it; in which case, the main neurotransmitter involved is the acetylcholine in the upregulation of some genes that participate in the chromosomal instability [29].…”
Section: Is Autonomic Dysreflexia Responsible For Other Comorbidities In Sci?mentioning
confidence: 99%